Integrating scientific cyberinfrastructures to improve reproducibility in computational hydrology: Example for HydroShare and GeoTrust. (July 2018) - Essawy, Bakinam T.; Goodall, Jonathan L.; Zell, Wesley; Voce, Daniel; Morsy, Mohamed M.; Sadler, Jeffrey; Yuan, Zhihao; Malik, Tanu
Abstract: The reproducibility of computational environmental models is an important challenge that calls for open and reusable code and data, well-documented workflows, and controlled environments that allow others to verify published findings. This requires an ability to document and share raw datasets, data preprocessing scripts, model inputs, outputs, and the specific model code with all associated dependencies. HydroShare and GeoTrust, two scientific cyberinfrastructures under development, can be used to improve reproducibility in computational hydrology. HydroShare is a web-based system for sharing hydrologic data and models as digital resources including detailed, hydrologic-specific resource metadata. GeoTrust provides tools for scientists to efficiently reproduce and share geoscience applications. This paper outlines a use case example, which focuses on a workflow that uses the MODFLOW model, to demonstrate how the cyberinfrastructures HydroShare and GeoTrust can be integrated in a way that easily and efficiently reproduces computational workflows. Highlights: Method for packaging and publishing scientific workflows. Integration between GeoTrust and HydroShare projects. GeoTrust is used to easily package environmental models as containers. HydroShare is used to document and share packaged workflows. An example application is provided for using a MODFLOW-NWT model.